Calcitriol induces post-thawed bovine sperm capacitation - Liaudat, Ana Cecilia (2023)
Background: Capacitation is a set of physiological changes sperms undergo to acquire fertilizing capacity. In vivo, this process is directly associated with high calcium levels in sperm cytoplasm. Calcitriol, the vitamin D hypercalcemic metabolite, is related to human sperm motility, capacitation, and acrosome reaction. This work aimed to study the effect of calcitriol on bull sperm quality parameters and capacitation. Methods: One million freeze-thawed spermatozoa were obtained from different bulls and treated with 20 nM of calcitriol for 30 min. Untreated cells (negative control) and treated ones with calcitriol or heparin (100 µg/mL, positive capacitation control) were evaluated for motility, viability, and functional parameters. Menadione (70 µM, 30 min) treatment was included as a reactive oxygen species (ROS) positive sperm agent. Results: The results elucidated that sperm exposed to 20 nM calcitriol showed higher viability, vigor, and capacitation than their positive and negative controls. The percentage of sperm with intact plasma and acrosome membranes, mitochondrial membrane potential (ΔΨm), and phosphatidylserine externalization was similar in all the conditions evaluated, while ROS production was higher with heparin and menadione-treated groups than the calcitriol group or negative control. Conclusion: Our results indicate that calcitriol induces the capacitation of thawed bull spermatozoa and maintains acceptable values of progressive motility, viability, and vigor without altering key biological parameters such as redox status, ΔΨm, and cell death.